2014
DOI: 10.1007/s00167-014-3186-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the morphology of the trochlea and the distal femur

Abstract: We have found that although the female distal femur is relatively narrower (larger AP/ML aspect ratio) than the male in three of the four measured levels, there is no significant difference between genders at the level of the anterior edge of the anterior chamfer. It is at this level that it has been suggested that impingement between soft tissues and an overhanging prosthesis is most likely to be painful. Equally, there were no gender-related differences in the shape of the trochlea. These data therefore do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 34 publications
5
20
1
Order By: Relevance
“…Lesions in the trochlea had the highest bias in measurement, as previously reported 19 . Variability in the contour of the trochlea 33,34 makes manipulating instruments arthroscopically to obtain accurate measurement especially difficult and may explain this variation. In contrast, the sizing of patellar defects had the smallest variability.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions in the trochlea had the highest bias in measurement, as previously reported 19 . Variability in the contour of the trochlea 33,34 makes manipulating instruments arthroscopically to obtain accurate measurement especially difficult and may explain this variation. In contrast, the sizing of patellar defects had the smallest variability.…”
Section: Discussionmentioning
confidence: 99%
“…Gender identification of the human skeleton is important in bioarchaeological and forensic practice and is widely established, as demonstrated by numerous reports, for example on the trochlea, distal femur (Pinskerova et al, 2014), humerus (Kranioti and Michalodimitrakis, 2009), pelvis (Papaloucas et al, 2008) and cranium (KemkesGrottenthaler et al, 2002;Balci et al, 2005). Gender differences in bone morphology have also been reported to exist in many other animal species, such as the badger (Hidaka et al, 1998), dog (Kieser and Groeneveld, 1992a;Sajjarengpong et al, 2003), elephant (Todd, 2010), medaka fish (Shanthanagouda et al, 2014), moose (Duetsch and Peterson, 2012), raccoon dog (Hidaka et al, 1998;Kim et al, 2012;Jurgel_ enas, 2015) and red fox (Jurgel_ enas, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…42 There were no gender differences present in the maximal trochlear depth, a result similar to the findings of Pinskerova et al, who found no sex differences existed in trochlear depth measurements standardized for femoral size. 43 While racial differences in distal femur geometry have been described for other parameters, 17 we are unaware of any literature comparing trochlear depth between races. Referenced from the vertical: a beam oriented directly vertically corresponds to a beam orientation of 0 degrees.…”
Section: Discussionmentioning
confidence: 99%